(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The occurrences of different surgical affections are very common in Bangladesh. The aim of this study was to determine the occurrence of most common surgical affections and their risk factors in calves and goat at Jhenidah Sadar Upazila of Bangladesh during the period from July to December 2011. Thirty seven (37) calves and twenty two (22) goats were used for this study. All animals were brought to hospitals with the complaints of surgical conditions. In this study we found umbilical hernia (59.5%), umbilical abscess (10.8%), atresia ani (8.1%), intestinal prolapse (2.7%), fracture of jaw (2.7%), necrosis of eyeball (2.7%), congenital polypus (2.7%), naval myiasis (5.4%) and abscess (5.4%) in calves. In case of goats, gid disease (36.4%), testicular hernia (4.5%), subcutaneous cyst (13.6%), atresia ani (4.5%), myiasis (9.1%), block of urethra (4.5%), fracture (9.1%), stitch abscess (9.1%), abscess (4.5%) and hematocele (4.5%) were recorded. The young, male and crossbred calves were showed more affections than that of adult and female. It was also found that the young male goats were more significantly (p<0.05) prone to surgical affections than that of adult and female. The male calf with 1-3 months of age (84.6%) were higher than that of male with age <1 month (70.8%). In both calf and goat, the female were found comparatively lower rate of surgical affections than male. However, further extensive work is very imperative to identify the specific cause as well as any factors that may influence region to region. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 394-397